One-Pot Synthesis of 1-Alkoxyisoquinoline Derivatives via Ru(II)-Catalyzed Aryl C−H Activation and Alkyne Annulation - Hazarika, Nitumoni; Gogoi, Nitish Nayan; Gogoi, Manashjyoti; Ghosh, Nayan; Das, Animesh (Synlett, 2025)
A one-pot synthesis of 1-alkoxyisoquinolines via ruthenium(II)-catalyzed aryl C−H activation and annulation with internal alkynes has been demonstrated. The reaction involves in situ generation of a benzimidate ester by the addition of nucleophilic alcohols and it acts as an “automatic directing group” (DGauto) for the aryl C−H activation and subsequent alkyne annulation. In contrast to conventional nitrogen-containing DG-assisted annulation approaches, this DGauto-assisted annulation of alkynes via C−H activation is advantageous as it reduces the number of reaction steps, simplifies the experimental procedure, and allows for easier handling of the corresponding precursors. Based on preliminary experimental observations, a plausible mechanism is disclosed for this transformation. Interestingly, most of the compounds show intense fluorescence emission, and their absorption and emission spectra are also presented in this work.
Keywords: Alkynes; Annulation; Ruthenium catalysis; Heterocycles; Homogeneous catalysis